2020
DOI: 10.1039/d0fo01948h
|View full text |Cite
|
Sign up to set email alerts
|

A polysaccharide from Fagopyrum esculentum Moench bee pollen alleviates microbiota dysbiosis to improve intestinal barrier function in antibiotic-treated mice

Abstract: Antibiotics are the most commonly used clinical drug for anti-infection, but they can also destroy normal microorganisms and cause intestinal barrier dysfunction. To elucidate the effects and mechanism of water-soluble...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…Furthermore, WFPP was correlated with reduced inflammatory response and enhanced intestinal sIgA secretion. In addition, 16S rDNA sequencing results showed that WFPP ameliorated gut microbiota dysbiosis induced by ceftriaxone, and especially that it regulated the populations of Proteobacteria (sIgA-secretion-related bacteria) and Enterococcus (inflammation-related bacteria) [148].…”
Section: Metabolic Syndromementioning
confidence: 97%
“…Furthermore, WFPP was correlated with reduced inflammatory response and enhanced intestinal sIgA secretion. In addition, 16S rDNA sequencing results showed that WFPP ameliorated gut microbiota dysbiosis induced by ceftriaxone, and especially that it regulated the populations of Proteobacteria (sIgA-secretion-related bacteria) and Enterococcus (inflammation-related bacteria) [148].…”
Section: Metabolic Syndromementioning
confidence: 97%
“…The extraction methods of polysaccharides focus on the traditional method, after 96% ethanol ( 175 ) or ultrasonic assist ( 30 ) solvent to skim the lipid, hot water ( 163 , 176 178 ) is used to extract the polysaccharide, and then a quadruple volume of absolute ethanol precipitates ( 163 , 176 , 178 ). Solid-phase extraction ( 9 , 174 ) as well as DEAE-52 cellulose column ( 20 , 177 , 178 ), Zorbax Carbohydrate Analysis Column ( 132 ) and other columns were used to separate the polysaccharides.…”
Section: Processing Techniques Applied In Bee Productsmentioning
confidence: 99%
“…Solid-phase extraction ( 9 , 174 ) as well as DEAE-52 cellulose column ( 20 , 177 , 178 ), Zorbax Carbohydrate Analysis Column ( 132 ) and other columns were used to separate the polysaccharides. High-performance liquid chromatography (HPLC), HPAEC-PAD ( 174 ), Fourier transform infrared (FT-IR) spectroscopy ( 20 , 178 ), gas chromatography (GC) ( 175 ), high-performance gel permeation chromatography ( 176 ), GC-MS ( 177 ), 13 C NMR ( 177 179 ), and HPLC-RID ( 132 ) techniques were used to identify the polysaccharides.…”
Section: Processing Techniques Applied In Bee Productsmentioning
confidence: 99%
“…The extraction methods of polysaccharides focus on the traditional method, after 96% ethanol (175) or ultrasonic assist (30) solvent to skim the lipid, hot water (163,(176)(177)(178) is used to extract the polysaccharide, and then a quadruple volume of absolute ethanol precipitates (163,176,178). Solidphase extraction (9,174) as well as DEAE-52 cellulose column (20,177,178), Zorbax Carbohydrate Analysis Column (132) and other columns were used to separate the polysaccharides.…”
Section: Sugars/polysaccharidementioning
confidence: 99%
“…Solidphase extraction (9,174) as well as DEAE-52 cellulose column (20,177,178), Zorbax Carbohydrate Analysis Column (132) and other columns were used to separate the polysaccharides. High-performance liquid chromatography (HPLC), HPAEC-PAD (174), Fourier transform infrared (FT-IR) spectroscopy (20,178), gas chromatography (GC) (175), high-performance gel permeation chromatography (176), GC-MS (177), 13 C NMR (177)(178)(179), and HPLC-RID (132) techniques were used to identify the polysaccharides.…”
Section: Sugars/polysaccharidementioning
confidence: 99%